The Islamic Republic of Afghanistan : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for The Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Afghanistan's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The program sets out a structural reform agenda that focuses on institution building, fiscal and financial reforms, and measures to combat corruption to lay the foundations for scaled up private sector development. The envisaged reforms dovetail with Afghanistan's National Development Framework currently being finalized. The program aims to preserve macro-financial stability by implementing prudent fiscal, monetary, and financial policies, and by maintaining external buffers and a flexible exchange rate regime. The IMF staff supports the authorities' request for an ECF arrangement under an IMF-supported program.